Hubungan Kecanduan Smartphone dengan Nomophobia Di Kalangan Remaja di SMA Negeri 5 Padang - Fitri, Tiwi Zulira; Wahyudi, Eri; Syafitri, Rika (Jurnal Sains Farmasi Dan Kesehatan, 2026)
The phenomenon of intensive smartphone use among teenagers has led to various psychological impacts, one of which is nomophobia, a condition characterized by excessive fear or anxiety when unable to access or use a smartphone. In West Sumatra, the highest percentage of smartphone users is among teenagers who are currently in high school or equivalent levels, with a usage rate reaching 39.28%. This study aims to determine the relationship between smartphone addiction and nomophobia among teenagers at SMA Negeri 5 Padang. The research uses a quantitative approach with a descriptive-analytic design, conducted from February to August 2025, with the data collection period from May 14 to May 20, 2025. The study population consisted of 819 students, with a sample of 98 students selected using proportional stratified random sampling. Data were collected using a questionnaire and analyzed univariately and bivariately using the Chi-Square statistical test. The results of the study show a significant relationship between smartphone addiction and nomophobia among students at SMA Negeri 5 Padang. The findings indicate that 51.8% of respondents experienced smartphone addiction, with a moderate level of nomophobia. The results also show a significant p-value (≤ 0.05) and a strong positive correlation (r = 0.00), meaning that the higher the level of smartphone addiction, the higher the level of nomophobia experienced by the students. In conclusion, this study confirms a significant relationship between smartphone addiction and nomophobia among teenagers at SMA Negeri 5 Padang. It is recommended that the school play an active role in increasing students' awareness of the negative impacts of smartphone use by providing regular counseling and guidance sessions related to healthy smartphone usage.